Analisis Isu Sosial dalam Meningkatkan Kesejahteraan Masyarakat - Sabrina Rizkia Fasha; Niswatun Hasanah; Hikmah Auliya; Nina Febriana; Fawwaz Fadhel Nugroho; Wafiq Aziz Matondang (Prosiding Seminar Nasional Ilmu Pendidikan, 2026)
Community welfare is one of the main goals in national development, yet various social issues such as unemployment, social inequality, weak character education, human rights problems, and low social awareness still hinder the realization of equitable welfare in society. This study aims to analyze social issues and their role in improving community welfare in Indonesia. The research used a qualitative descriptive approach through library research by collecting data from scientific journals, articles, books, and official documents related to social welfare and social issues. The findings indicate that unemployment has a significant impact on economic conditions and poverty levels, while rapid digital development influences the character formation of younger generations. In addition, fair law enforcement and the implementation of human rights contribute to social stability and public trust. The study also found that educational interaction through counseling, social education, and community activities plays an important role in increasing social awareness and strengthening solidarity within society. The implication of this study shows that improving community welfare requires integrated efforts involving economic development, character education, social justice, and active community participation in addressing social issues.